2018
DOI: 10.2147/cia.s154418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multimorbidity in subjects aged ≥60 years in a developing country

Abstract: BackgroundAging is one of the most prominent features in recent population dynamics around the world. As populations age, the prevalence of simultaneous chronic diseases increases, which is known as multimorbidity.ObjectiveThe aim of the present study was to determine the prevalence of multimorbidity and associated factors in a sample of elderly Mexican subjects.Materials and methodsA cross-sectional descriptive study was performed on a convenience sample of 139 subjects aged ≥60 years. The dependent variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
1
21
0
3
Order By: Relevance
“… 27 Most of the studies (n = 46, 60.5%) had a primary purpose of reporting the prevalence and patterns of multimorbidity. Of the total 76 studies, 52 (68.4%) were conducted in only six middle-income countries: Brazil, 27 42 China, 43 54 South Africa, 25 , 26 , 55 64 India, 65 72 Mexico 73 , 74 and Iran. 75 , 76 Studies based on multicountry data (n = 11) were based on data obtained from the World Health Organization’s (WHO’s) Study on Global Ageing and Adult Health (SAGE) and World Health Surveys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Most of the studies (n = 46, 60.5%) had a primary purpose of reporting the prevalence and patterns of multimorbidity. Of the total 76 studies, 52 (68.4%) were conducted in only six middle-income countries: Brazil, 27 42 China, 43 54 South Africa, 25 , 26 , 55 64 India, 65 72 Mexico 73 , 74 and Iran. 75 , 76 Studies based on multicountry data (n = 11) were based on data obtained from the World Health Organization’s (WHO’s) Study on Global Ageing and Adult Health (SAGE) and World Health Surveys.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of multimorbidity seemed to have a pattern of increasing prevalence with increasing age. It ranged from 3.2% (93) to 67.8% 37 among adults aged 18 or older, 19.4% 76 to 80% 59 among people aged 40 and older, and 27.3% 74 to 90.5% in participants aged 60 and older. 52 The prevalence in the general population was also found to be higher in females (25%–52.2%) (54, 75) than males (13.4%–38.6%).…”
Section: Prevalence Of Multimorbiditymentioning
confidence: 99%
“…The prevalence of multimorbidity was higher than that of our research, probably because the survey data were of national origin. In addition, a study in a developing country also showed that the prevalence rate of multimorbidity in women is higher than that in men for people over 60 years old [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We measured several oral health indicators. This secondary analysis is part of a larger study, some of whose results have been previously published 1520. Inclusion criteria were as follows: 1) aged at least 60 years and 2) willingness to participate in the research (permission granted from either the participant or their relatives).…”
Section: Methodsmentioning
confidence: 99%